Determining of Passenger Load Factor for Public Bus Transportation in Northern Peninsular Malaysia - Norhisham S.; Azlan N.N.I.M.; Bakar M.F.A.; Saad N.M.; Fauzi W.A.F.W.M.; Masjuki S.A.; Ramli M.Z.; Samsudin S.S. (Springer Science and Business Media Deutschland GmbH, 2023)
Bus transportation; Buses; Developing nations; Load factors; Malaysia; Northern peninsular malaysia; Passenger loads; Public bus; Public transportation; Quality-of-service; Social mobility; Well being; Quality of service